Проєкт гарячого цеху в кафе на 60 місць - Тараканов, Роман Олександрович (My University, 2026)
Бакалаврський кваліфікаційний проєкт присвячений розробці проєкту гарячого цеху кафе «Aneid» – літературного закладу, назва якого натхненна безсмертною «Енеїдою» Івана Котляревського, батька нової української літератури, який тривалий час мешкав у Полтаві. Кафе планується розташувати в історичному центрі міста за адресою вулиця Соборності, 24. Вибір локації обґрунтований високою пішохідною прохідністю (понад 5 000 осіб на добу), близькістю до Музею І. Котляревського, Полтавського академічного театру та основних ділових центрів, що забезпечує стабільний потік цільової аудиторії. На основі розрахунку добової динаміки попиту, що враховує місткість зали (60 місць), режим роботи (з 9:00 до 21:00) та коефіцієнти оборотності й заповнення, встановлено загальну кількість відвідувачів за добу – 303 особи, при цьому оборотність одного місця становить 5,05, що значно перевищує середньогалузеві показники (2 – 3) завдяки запровадженню кавової зони takeaway, яка генерує до 40% ранкового потоку. Меню кафе включає 41 позицію, з яких 27 виробляються в гарячому цеху (супи, гарячі закуски, другі страви, гарніри, соуси), що дозволяє охопити широкий спектр смаків та забезпечити збалансоване харчування для різних категорій гостей. Фірмовою стравою закладу обрано «Свинячу шию по-полтавськи, мариновану в темному пиві з медом та гірчицею, витриману за технологією sous-vide, подану з печеним яблуком та яблучно-хріновим соусом». Інноваційність страви полягає у застосуванні низькотемпературного вакуумного приготування (62 °C, 4 години), яке за даними наукових досліджень дозволяє знизити втрати маси з 37% до 8% порівняно з традиційним смаженням, максимально зберегти вітаміни групи B та незамінні амінокислоти, а також забезпечити рівномірне прогрівання продукту по всій товщі. Використання локальної сировини – темного полтавського пива та яблук сорту «Сніжний кальвін» - підкреслює регіональний гастрономічний код. Для реалізації виробничої програми (350 порцій на добу, загальна вага ≈ 68 кг) підібрано сучасне теплове та холодильне обладнання з наведенням актуальних посилань на українських постачальників, а також допоміжне обладнання українського виробництва. Загальна площа стаціонарного обладнання становить 10,41 м², розрахункова загальна площа гарячого цеху – 35,0 м² (5×7 м) при коефіцієнті використання 0,30, що відповідає нормативним вимогам. Дизайн-концепція «Літературна кав’ярня з сучасним акцентом» реалізується через відкриту кавову вітрину, книжкові стелажі з творами полтавських письменників (І. Котляревського, Панаса Мирного, В. Короленка, М. Старицького), колірну гаму (темно-зелений, бежевий, цегляний) та індустріальні елементи. Фасад оздоблено об’ємними літерами «ANEID» з LED-підсвіткою та крейдовою дошкою з цитатами з «Енеїди». Пояснювальна записка БК проєкту викладена на 76 сторінках, містить 13 таблиць, 7 рисунків. This bachelor’s qualification project is dedicated to the design of the hot shop for the “Aneid” cafe – a contemporary literary establishment located in the historic heart of Poltava at 24 Sobornosti Street. The name “Aneid” deliberately references the immortal poem “Aeneid” by Ivan Kotlyarevsky, the founder of modern Ukrainian literature, who lived and worked in Poltava for a long time. The selection of this location is not accidental: Sobornosti Street is one of the main pedestrian and transport arteries of the city, connecting key cultural and business centres of Poltava, and is characterized by high pedestrian traffic (over 5,000 people per day) and proximity to the Ivan Kotlyarevsky Museum. All this ensures a stable flow of potential customers, including office workers, tourists, students, families with children and freelancers. To calculate the daily demand dynamics, a methodology was used that takes into account the number of seats (60), the operating hours (from 9:00 to 21:00, 12 hours per day), as well as the turnover of one seat per hour and the occupancy rate of the hall, the values of which were determined based on regulatory data for general-type cafés adjusted for the specificity of the concept. According to the calculations, the total number of visitors per day is 303 persons, while the turnover of one seat reaches 5.05, which significantly exceeds the industry average (2 – 3 for general-type cafés). This high figure is achieved by introducing a separate coffee zone with take-away drinks, which generates up to 40% of the total flow, ensuring high throughput of the establishment, especially in the morning hours from 9:00 to 11:00, and creating an additional financial flow without overloading the hot shop’s production capacity. The café menu comprises 41 items, of which 27 are produced directly in the hot shop. These include soups (borscht, chicken noodle soup, pumpkin cream soup), hot appetisers (mushroom julienne, chicken wings in teriyaki sauce, cheese sticks), main courses (eight items, including the signature dish), side dishes (mashed potatoes, rice with vegetables, grilled vegetables) and sauces (cream, tomato, mushroom). The hot shop’s production programme, formed on the basis of the dish assortment, is calculated at 350 portions per day with a total weight of about 68 kg, with a predominance of main courses (120 portions) and soups (105 portions). The signature dish of the establishment is “Poltava-style pork neck marinated in dark beer with honey and mustard, cooked sous‑vide, served with baked apple and apple‑horseradish sauce”. The innovation of the dish lies in the application of the low‑temperature vacuum cooking method (62 °C for 4 hours). According to research, the “Sous Vide” technology ensures uniform heating of the product throughout its thickness, prevents evaporation of moisture and volatile aromatic substances, reduces weight loss from 37% during traditional cooking to 8%, and extends the shelf life of the finished semi-finished product. In addition, the use of local raw materials (dark Poltava beer, “Snizhny Kalvin” apples) emphasises the regional identity of the dish, while the contrasting spicy sauce of baked apples and horseradish creates an interesting flavour balance, complementing the fattiness and sweetness of the main product. To fulfil the production programme, a set of modern thermal, refrigeration and auxiliary equipment available on the Ukrainian market has been selected, as well as a wide range of auxiliary non‑mechanical equipment of Ukrainian production. The total area of the hot shop, calculated using the usable area method with a utilisation coefficient of 0.30, is 35.0 m² (dimensions 5×7 m), which exceeds the regulatory minimum for a 60‑seat cafe (24 m²) and provides the necessary space for free movement of personnel, placement of auxiliary equipment and compliance with sanitary and hygienic requirements. The design concept “Literary coffee house with a modern touch” is implemented through an open coffee display (guests watch the drink preparation process), book shelves with thematic literature (works by Ivan Kotlyarevsky, Panas Myrny, Volodymyr Korolenko and other writers associated with Poltava), a colour palette (dark green, beige, brick) and industrial details. The explanatory note of the bachelor’s project has 75 pages, contains 13 tables, 7 figures.
Keywords: кафе; гарячий цех; технологічне обладнання; виробнича програма; літературна концепція; кава на виніс; sous‑vide; Полтава; Іван Котляревський; cafe; hot shop; technological equipment; production programme; literary concept; coffee to go; sous‑vide; Poltava; Ivan Kotlyarevsky